Propuesta metodológica para el desarrollo de la conciencia ambiental en estudiantes de la Institución Educativa Los Licenciados de Ayacucho - 2019 - Vargas Meneses, Rosario (2021)
This research entitled "Methodological proposal for the development of environmental awareness in students of the Educational Institution Los Licenciados de Ayacucho - 2019", developed in order to determine the influence of the application of the methodological proposal for the development of environmental awareness in students of the educational institution mentioned. It was specified through the design of pre-experimental research. The data collection work was carried out through an observation sheet which allowed determining the influence of the independent variable on the dependent. The statistician used in the present investigation was Wilcoxon to determine the difference between the pre test and the post test, with a significance level of 5% (0.05). The results obtained through the Wilcoxon statistician, show us that the methodological proposal significantly influences the development of environmental awareness in students in the fourth year of secondary school of the Educational Institution Los Licenciados de Ayacucho– 2019; because there is a clear difference between the pre test and post test achieving a significant increase in environmental awareness (0.000 <0.05).